Between equality and discrimination: the paradox of the women's game in the mind-sport bridge. Issue 4 (2nd October 2022) - Rogers, Ashley; Snellgrove, Miriam; Punch, Samantha
ABSTRACT: Gender differences in the sporting world are long-standing and historic. Couched often as biologically given, differences in the uptake, training and playing of sport, from hobby to elite Olympian, are riven with discourses, practices and attitudes regarding the different aptitudes of men and women. Recognizing the ways these gendered differences operate is contentious and problematic, particularly in relation to women-only spaces. Such spaces can be used to promote the development and skills of women while simultaneously perpetuating and reinforcing women's difference and inequality to men. Using the case study of bridge (the card game), we analyse the ways in which the women's game is viewed as both hindering women's progression in the game whilst also providing women spaces to compete internationally. Findings from an email questionnaire with tournament and club players show how the women's game incapsulates both inequality and opportunity. The women's game remains a divisive issue within the bridge world as it provides competitive opportunities for women at an elite level, whilst simultaneously being viewed as technically inferior and discriminatory. The paper argues that the tensions and ambivalences of the paradox of women-only spaces reflect ongoing hetero-patriarchal discourses within sporting and leisure contexts.